2004
DOI: 10.1021/es034659r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Remineralization on Heavy-Metal Leaching from Cement-Stabilized/Solidified Waste

Abstract: Crushed samples of stabilized/solidified (s/s) waste were leached at constant leachate pH in the pH range 4-7 with nitric acid solutions to evaluate the influence of remineralization on metal release. The s/s waste consisted of synthetic heavy-metal sludge containing 0.1 mol L(-1) copper nitrate, 0.1 mol L(-1) zinc nitrate, and 0.1 mol L(-1) lead nitrate mixed with ordinary Portland cement. Unleached and leached particles were characterized by scanning electron microscopy and energy-dispersive X-ray spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 12 publications
3
18
0
2
Order By: Relevance
“…Islam et al (2004a) also found a diffusion-dependent rate of reaction in cement paste being attacked by acid in their batch experiment.…”
Section: Sandstone-cement Experimentsmentioning
confidence: 90%
“…Islam et al (2004a) also found a diffusion-dependent rate of reaction in cement paste being attacked by acid in their batch experiment.…”
Section: Sandstone-cement Experimentsmentioning
confidence: 90%
“…Mohammad found the consumption of ANC in cement matrix forms two consecutive leaching fronts, the leaching of Zn and Pb only occurs between the second front and the specimen surface, and the leaching behavior of metals is modeled by the shift of the fronts (Mohammad et al 2004a). Mohammad also found the shift of the fronts is influenced by pH (Mohammad et al 2004b). These conclusions have supported our inference about the three-stage release.…”
Section: Release Behavior Of Pbmentioning
confidence: 93%
“…Each leaching test lasted for approximately 150 h. Leachate samples were collected at regular time intervals during the tests and analyzed by inductively coupled plasma-atomic emission spectroscopy (ICP-AES). The concentrations of major ions and trace metals in the leachate as a function of leaching time are presented in Islam et al [16].…”
Section: Methodsmentioning
confidence: 99%
“…The condition of equilibrium would require that the composition of pore water be uniform in the crushed material and equal to that of the extract. However, backscattered SEM images revealed that the leaching front marking the dissolution of Ca-Al hydroxy sulfates only advanced between 30 and 220 µm from the surface toward the interior of s/s waste particles leached for 150 h at constant pH in the range pH 4-7 [16,17]. Since a large change in pore water composition occurs across this front, uniformity of pore water composition (i.e., equilibrium) was not achieved even for this large extraction time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation